Commentary: The Use of Case-based Learning and Concept Mapping to Teach Students Clinical Reasoning - Jeremy R. Hawkins; Michael Reeder; Michael Olson; Amy Bronson (Bowling Green State University, 2019)
Introduction: Teaching students as inexperienced clinicians the process of evaluating athletic injuries and medical conditions is often challenging. Utilizing case-based learning and concept mapping as educational tools can facilitate growth in the clinical and diagnostic decision making process. Discussion: Experienced clinicians regularly employ case pattern recognition and hypothetico-deductive reasoning in clinical settings. Each type of reasoning is prone to anchoring and confirmation bias, devaluing relevant information, and framing effect if not utilized correctly. Classroom instructors and preceptors can use case-based learning and concept mapping to help students as inexperienced clinicians organize their thinking and more effectively apply their knowledge. Implications: The use of case-based learning and concept mapping to teach the process of evaluating athletic injuries and medical conditions can help students as inexperienced clinicians: improve clinical reasoning skills; decrease bias; develop more efficient and effective clinical reasoning; become more confident in what steps come next; value clinical data equally and impartially; and more effectively use hypothetico-deductive reasoning.